Internationalisation and Professionalisation in Teacher Education Challenges and Perspectives - Linhofer, Susanne; Haas-Vogl, Heiko; Holz, Oliver (Studienreihe der Pädagogischen Hochschule Steiermark, 2023)
The need for internationally and interculturally competent teachers is rising due to the increasing globalisation of society resulting in in-creased linguistic and cultural diversity in today's classrooms. As a European mobility and education programme, Erasmus has become a cornerstone of the internationalisation of European higher education institutions over the last three decades. The 16th volume of the study series of the University of Teacher Edu-cation Styria aims to disseminate results and products of international cooperation to ensure their sustainability. Authors focus on project results, international experiences and best practices as well as benefi ts and challenges of international networking, cooperation projects and research activities.